MARKETING STRATEGY FOR RICE COMMODITIES AT THE NAWANG JAYA TRADING BUSINESS IN BARAS, NANGA BARAS DISTRICT, SAMBI RAMPAS DISTRICT, EAST MANGGARAI DISTRICT - Nawa, Yeremias M.; Benu, Frederik L.; Olviana, Tomycho (Undana Press, 2025)
This research was conducted at Nawang Jaya Trading Business in Baras, East Manggarai Regency. This research aims to determine the internal and external conditions of Nawang Jaya Trading Business and marketing strategy for rice products at Nawang Jaya in the data collection method used in this research is through observation, interviews and documentation. The sample was determined using purposive sampling. The types of data collected are primary data and secondary data. The data analysis used is SWOT analysis. The results of the research show that (1) from internal factors it can be concluded that strengths have a value of 1.93 and weaknesses have a value of 0.9. This means that in the marketing strategy for rice products Nawang Jaya Trading Enterprises still has better strengths. from existing weaknesses. (2) From external factors it is concluded that opportunities (Opportunity) have a score of 1.59 and threat factors (Threats) have a value of 1.04, indicating that there is still an opportunity for a marketing strategy for Nawang Jaya Trading Enterprise rice products, considering the threats smaller than chance. The marketing strategy implemented through intensive strategies, namely market penetration, market development and product development.